DIGITALISASI PEMASARAN SERTA PENDAMPINGAN MANAJEMEN USAHA PADA UMKM ANGKRINGAN KMS DI TUMPANG KABUPATEN MALANG - Iklila Amiroh; Dita Rahmi Rahayu; Agung Winarno; Agus Hermawan (Rafandha Press, 2022)
The development of MSMEs is increasingly rapid, not spared from increasingly fierce competition. The emergence of MSME competition if it is not balanced with adequate management, it will be difficult to develop and will be worse off being beaten by its competitors. Therefore digital marketing through social media and online marketplace platforms is urgently needed at this time. However, many MSME actors ignore digital marketing due to a lack of knowledge about technology. This also happened to the